Potensi Novelty Bidang Injection Mold Design: Visualisasi Pemetaan Bibliometric - Rahman Hakim; Widodo Widodo; Benny Haddli Irawan; Ahmad Nurasa; Amar Makruf (Politeknik Negeri Batam, 2020)
This study aims to determine the direction of development in the world of Mold & Dies design in the world. Data searches were carried out through science direct databases using the design of molds and dies as keywords with a limitation of open access journals between 2015 - 2020. The results were comprehensively analyzed based on year, publisher's name, institution, and the country as well as research subjects. Files from Mendeley software are saved in Reference Manager Format (.RIS) format which is processed into VOSviewer software to find out the bibliometric map. The results revealed that the highest number of publications is in a procedia manufacturing journal. The most contributing country in the European continent indexed in Scopus is Germany. Within the output in the form of network visualization, it is found that several novelty potentials are in line with the direction of the development of the study with the parameters of the number of population and the year of the research output. Publications on the most similarity and chance of novelty on research topics are in Cluster 1, which consists of Energy Efficiency, Decision Process, Plastic Materials, and Sustainability.Keywords: Novelty, Injection Mold Design, Bibliometric Maping, VOSviewer